Somatic expression of the testis-specific PDHA2 gene : mechanisms of activation/silencing - Pinheiro, Ana Sofia da Costa, 1981- (2012)
Tese de doutoramento, Farmácia (Biologia Celular e Molecular), Universidade de Lisboa, Faculdade de Farmácia, 2012